2014
DOI: 10.2478/amm-2014-0285
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of Surface Layer of Carburized 38CrAlMo6-10 Steel Subjected to Nanostructurization by a Heat Treatment Process/ Struktura I Właściwości Warstwy Naweglanej Na Stali 38Cralmo6-10 Po Procesie Nanostrukturyzacji W Warunkach Obróbki Cieplnej

Abstract: The aim of the study was to produce and characterize a nanobainitic microstructure in surface layers of carburized 38CrAlMo6-10 structural steel. Steel contained 1.% Al and 0.3% Si -elements hindering the cementite precipitation, which was considered to be adequate for obtaining a carbide free bainite. Steel samples were subjected to two different vacuum carburizing processes in order to obtain two different contents of carbon in surface layer. To produce a nanobainitic microstructure a heat treatment consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…On the other hand, the solution strengthening helps reduce the thickness of the resulting bainitic ferrite plates [ 46 ]. The influence of carbon concentration on the size of bainitic transformation products was deliberately used by Wasiluk et al [ 13 ] and Skołek et al [ 14 ] to obtain nanobainite in carburised steels. However, in our studies, we observed the coarsening effect of the bainitic ferrite plates in the transition zone of the substrate ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the solution strengthening helps reduce the thickness of the resulting bainitic ferrite plates [ 46 ]. The influence of carbon concentration on the size of bainitic transformation products was deliberately used by Wasiluk et al [ 13 ] and Skołek et al [ 14 ] to obtain nanobainite in carburised steels. However, in our studies, we observed the coarsening effect of the bainitic ferrite plates in the transition zone of the substrate ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the research directions aiming to overcome these limitations is the use of surface carburising treatment prior to the nanobainitising process. The works by Wasiluk et al [ 13 ], Skołek et al [ 14 ], and Wang et al [ 15 ] should be mentioned here as examples of the effective application of combined carburising and nanobainitising. Hybrid treatments involving surface engineering also appear as a promising direction, expanding nanobainitic steels’ application areas.…”
Section: Introductionmentioning
confidence: 99%
“…Li [ 2 ] used bainitic steel, with a composition that ranged from 0.45% to 0.65% C, 2.00% to 4.00% Mn, 0.20% to 2.00% Si, to manufacture wear-resistant liners for mining machines that have more than double the service life under the same conditions than those made of Hadfield steel. With less hardness than martensitic steel, bainitic steel bearings show better wear resistance than martensitic steel bearings due to better toughness [ 3 , 4 ]. The increased toughness will further improve the wear resistance of the bearing [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…35 Participants also had the opportunity to familiarise themselves with research on modern technologies of steel nanostructuring achieved during the NanoStal project at the Faculty of Material Science and Engineering at Warsaw University of Technology. [20][21][22][36][37][38][39][40][41][42] The presented papers gave a good picture of the current state of the research on advanced steels and the latest achievements in structure and property control. They also helped to depict the directions in which the field should develop and potential areas where the research outcomes could be applied.…”
mentioning
confidence: 99%